Flexible Sigmoidoscopy Rather than Colonoscopy Is Adequate for the Diagnosis of Ipilimumab-Associated Colitis. Issue 3 (March 2019) - Herlihy, J. Daniel; Beasley, Stephen; Simmelink, Andrew; Maddukuri, Vinaya; Amin, Asim; Kamionek, Michal; Jacobs, Carl; Bossi, Krista; Scobey, Martin
Abstract : Objectives: Treatment with ipilimumab, a cytotoxic T lymphocyte antigen-4 approved for metastatic melanoma can result in clinically significant immune-mediated drug injury in the form of colitis. Timely diagnosis and response are essential for optimal management. The aims of our study were to determine the percentage of our patients with ipilimumab-associated colitis in which the colitis could be diagnosed by flexible sigmoidoscopy only and to describe the variations in endoscopic and histologic findings as well as the patients' clinical courses. Methods: We retrospectively reviewed 244 patients with metastatic melanoma, treated them with ipilimumab, and characterized the endoscopic and histologic features for those who developed colitis. Results: Of the 68 patients who presented with diarrhea, 33 were diagnosed as having ipilimumab-associated colitis. Endoscopically, all of them had involvement of the left side of the colon; none of the patients were noted to have isolated right colon involvement. Conclusions: Ipilimumab-associated colitis can be diagnosed with a flexible sigmoidoscopy alone, obviating the need for full colonoscopy. Abstract : Ipilimumab is approved for the treatment of metastatic melanoma and is associated with significant immune-mediated colitis. The authors reviewed 244 patients with metastatic melanoma treated with ipilimumab and characterized the endoscopic and histologic features of those who developed colitis. The authors showed that in all of the patients who developed ipilimumab-associated colitis, the left side of the colon was always involved, and diagnosis could be made with flexible sigmoidoscopy, thereby making colonoscopy unnecessary. The response to treatment was also characterized and showed that most patients responded well to medical management with steroids or infliximab.